The patient journey and burden of disease in Demodex blepharitis in the United States - Periman, Laura M.; Whitley, Walter O.; Maiti, Sathi; Mun, James; Ho, Anh N.; Oak, Bhagyashree; Athavale, Amod; Yeu, Elizabeth (Journal of medical economics, 2025)
blepharitis (DB) is a chronic eyelid disease caused by an infestation of mites. The objective of this chart audit study was to characterize the patient journey and burden of illness associated with DB from an eye-care provider's perspective. Retrospective medical data for patients with a confirmed diagnosis of DB were anonymously collected ophthalmologists and optometrists in the US (collectively eye-care providers [ECPs]), in June-July 2022. Each eligible ECP completed a questionnaire and provided chart abstractions of 1-5 medical charts of patients with DB in an electronic case report form. All ECPs ( = 61) were ophthalmologists or optometrists who worked primarily in office-based private practices (97%). Data from 192 medical charts of patients with an ECP-confirmed diagnosis of DB were abstracted and their demographics included 54% males and 71% Caucasians. The mean time (±SD) since diagnosis was 11 (±9.0) years. Over 40% of patients were not examined for DB at initial presentation, and the average time from initial presentation to a definitive diagnosis for DB was 6.5 months. After DB diagnosis and across the period of observation until the time of the study, patients had a mean (±SD) of 3.2 (±2.8) follow-up visits due to DB and continued to use multiple off-label prescription and over-the-counter therapies for symptom management. Medical records may be incomplete or inconsistently reported and subject to recall bias. The patient journey is lengthy with multiple challenges, including delay in DB diagnosis and recurring DB symptoms, underlining an urgent need for action to improve diagnosis and treatment of DB.